Effects of Chitosan, Peppermint Oil, and Orange Pectin-Based Edible Coatings on Cherry Tomato Quality - Muryeti, Muryeti; Anwar, Chadas Baiti Muhammad (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
Cherry tomatoes are nutrient-rich climacteric fruits that deteriorate rapidly after harvest. This study evaluated an edible coating containing orange pectin, chitosan, and peppermint oil for preserving cherry tomato quality during room-temperature storage. A two-factor completely randomized design was applied using chitosan concentrations of 0%, 1%, 2%, and 2.5% and peppermint oil concentrations of 0.5%, 1.0%, and 1.5%. Weight loss, total soluble solids, pH, vitamin C content, and sensory attributes were analyzed using two-way ANOVA. The coating reduced weight loss, slowed changes in total soluble solids and pH, improved vitamin C retention, and maintained color and texture compared with the untreated control. The combination of 1% chitosan and 1.5% peppermint oil generally produced the best overall results. Therefore, this formulation shows promise as an edible coating for maintaining the postharvest quality of cherry tomatoes stored at room temperature.